Reflexos de uma disputa: O dia sombrio e a noite clara na fotografia oitocentista - Reis, Luzo (2022)
In this article we will present two nineteenth century attitudes in photography toward the subject of the night. The first of them, the somber day of nineteenth-century photography, will address artistic experiences that produced images that were obscure, diffuse, or with the presence of pronounced shadows in reference to a nocturnal visuality applied to scenes originally taken during the day. The second, the nineteenth century clear night, will examine the endeavors of technical, scientific, or utilitarian photography in lighting the night to produce sharp and clear images. We hope to unveil how these two expedients reveal the participation of photography in the dichotomous arena of the nineteenth century that pitted light and shadow, reality and subjectivity.